Increasing pay related social insurance to fund the State Pension: Incidence and effectiveness - Karina Doorley; Dora Tuda (The Economic and Social Research Institute (ESRI), 2024)
Demographic change is putting pressure on the sustainability of State Pension systems in many developed countries. In Ireland, there have been recent calls to reform the system of contributions and/or increase the State Pension age in order to avoid significant shortfalls in the Social Insurance Fund (SIF), out of which the State Pension is paid. The Government of Ireland has committed to retaining the State Pension age at 66. In order to achieve this and maintain the viability of the SIF, it has also committed to increasing social security contributions through the Roadmap of Increases to Pay Related Social Insurance (PRSI), which will occur between 2024 and 2028. Using SWITCH, the ESRI's microsimulation model for Ireland, this paper assesses the consequences of these planned reforms, focussing on the amount of revenue they will raise, on the distribution of income and on financial incentives to work. Our analysis shows that the reforms proposed by the Roadmap will result in revenue gains of exteuro1.6 billion per annum by 2028. The reforms are progressive in nature, affecting high income households by more than low-income households. They affect men by slightly more than women due to their higher labour market participation. Across age-cohorts, the incomes of those aged 25-54 are estimated decrease the most. We estimate that the reforms will increase poverty rates slightly, particularly the child poverty rate. The proposed reforms slightly decrease the financial incentive to work, particularly for those in low-income households. We argue that further reform will be needed beyond 2028 to ensure the continued viability of the SIF, and suggest that policymakers may wish to consider some of the more structural reforms to PRSI and the SIF proposed by the Commission on Taxation and Welfare, the Commission on Pensions and the Irish Fiscal Advisory Council.
Keywords: 330